An imaging method for the evaluation of early atherosclerosis in inflammatory bowel disease: epicardial adipose tissue - Gozel, Nevzat; Eyvaz, Abdullah; Ozel, Banu Demet; Dogan, Yasemin; Sarli, Bahadir; Ozturk, Agah Bahadir; Poyrazoglu, Orhan Kursat (Mattioli 1885, 2019)
The aim of this study was to detect early atherosclerosis in patients with inflammatory bowel disease (IBD) that were strictly selected according to traditional cardiovascular risk factors, and to demonstrate whether evaluating epicardial adipose tissue can serve as an imaging modality through which to detect early atherosclerosis. Forty-three patients with IBD and 29 controls were enrolled in the study. Participants with well-known cardiovascular risk factors were excluded. Carotid intima media thickness (CIMT) and epicardial adipose tissue (EAT) were evaluated by the same physician blinded to the study groups. CIMT and EAT values were significantly higher in the IBD group when compared to the control group (p<0.01 and p<0.001, respectively). EAT was correlated with CIMT in the IBD group (r=0.574, p=0.001). CIMT and EAT are functional imaging methods that are used to detect early atherosclerosis in IBD patients without classic cardiovascular risk factors. EAT may be used as an additional diagnostic tool through which to detect early atherosclerosis in clinical practice in IBD patients.
Keywords: Inflammatory Bowel Disease; Atherosclerosis; Imaging Techniques; Chronic Diseases